Stop Reaganism March and Rally Courthouse Park - Watkins, Howard::::::::: (1982)
Women's International League for Peace and Freedom members carrying large banner "You Too Can Be A Star: Stop The Arms Race"; Ellie Bluestein on left Latin America Support Committee--Fresno banner in background